Volcanoes of the World : Third Edition - Siebert, Lee (Book collections on Project MUSE., 2010)
This impressive scientific resource presents up-to-date information on ten thousand years of volcanic activity on Earth. In the decade and a half since the previous edition was published new studies have refined assessments of the ages of many volcanoes, and several thousand new eruptions have been documented. This edition updates the book's key components: a directory of volcanoes active during the Holocene; a chronology of eruptions over the past ten thousand years; a gazetteer of volcano names, synonyms, and subsidiary features; an extensive list of references; and an introduction placing t.